Evaluation of the impact of climate change on reference crop evapotranspiration in Hamedan-Bahar plain. (5th April 2021) - Talebmorad, Hossein; Abedi-Koupai, Jahangir; Eslamian, Saeid; Mousavi, Sayed-Farhad; Akhavan, Samira; Ostad-Ali-Askari, Kaveh; Singh, Vijay P.
Climate change was simulated using the HADCM3 general circulation model and was downscaled using the LARS-WG downscaling model. After downscaling and uncertainty analysis, climatic parameters were generated until year 2090, assuming three emission scenarios A1, B1 and A1B. After fitting an equation for ETo, its future values were calculated for the simulation period. Results indicated an increase in the mean annual ETo under all three scenarios. The highest increase occurred under the A2 scenario and the lowest increase occurred under the B1 scenario. Comparison of monthly ETo values showed that although greenhouse gas emissions in the next 30-year period did not lead to a perceptible increase in ETo but severe long-term increase was predictable. According to predictions, the mean monthly ETo in the [cold months] in different scenarios did not change significantly and much of the increase occurring in the mean annual ETo was due to a significant increase in the monthly ETo in [hot months] of the year.